Hang-up IUD, New Technique for Suturing CuT-380A IUD to Uterine Fundus in Immediate Postplacental Insertion during Cesarean Delivery: Twelve Months Follow up - Tjahjanto, Hary (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: The aim of this study was to evaluate the effectiveness, side effects and acceptability of postplacental CuT-380A IUD insertion using new technique for suturing to uterine fundus during cesarean section (hang up technique). Method: Prospective cohort study of postplacental IUD CuT-380A insertion during cesarean delivery. Hang-up technique consists of performing a puncture in the center of the fundus wall using straight needle into the uterine cavity and subsequently using chromic catgut no. 1 to tie the IUD using anchor knot and hanging the IUD to the fundus. Our subjects were women who underwent caesarean delivery at dr. Kariadi Hospital between 1st June 2009 to 31st April 2011 and followed up at 12 months follow-up, one woman underwent IUD removal because of severe dysmenorrhea. No perforation or expulsion was reported. Conclusion: Immediate postplacental insertion of IUD CuT-380A using hang-up technique is safe and effective. Typical use effectiveness is high (Pearl Index 0.93) and there were no reported incidents of expulsion or perforation. Acceptance and continuation rate were high, 98.15% and 95.37% respectively. [Indones J Obstet Gynecol 2014; 2-31: 132-139] Keywords: anchor knots, cesarean section, hang-up IUD, postplacental IUD insertion